Effect of iDu (iLearning Education) on Lecturer Performance in the Lecture Process - Rahardja, Untung; Aini, Qurotul; Khoirunisa, Alfiah (Pandawan, 2018)
All fields have been supported by technology, especially in the world of education in theteaching and learning process to determine the quality of graduates of a university. In theworld of education Raharja College has implemented iLearning learning methods to achievelearning goals. Students are given learning experiences using the iLearning method which isthe learning process using the Ten Pillar IT iLearning (TPI) media. But the learning processis not working properly and is still using all the paper-based nuances such as learningmethods in general, of course it is considered to be ineffective and efficient. Therefore,nowadays to achieve highly effective learning goals so that the Learning ManagementSystem (LMS) is implemented using iDu where lecturers can provide assignments onlineanytime and anywhere easily that can convey information online, i.e. on the mediaapplication iDu via e-mail Rinfo. So that with the delivery of information via E-mail Rinfo canbe done anywhere and anytime without having to come to campus which of course has aninfluence on the performance of lecturers in giving assessments to students, besides that theinformation delivered is more comprehensive and precise to students not limited by spaceand time.